Geometric Investigation of Al-Wind Dam Reservoir Northeastern Iraq, using Digital Elevation Models and Spatial Analyses System - Sabbar A. Saleh; Iktifaa T. Abdul Qadir; Amin M. Ibrahim; Huda M. Hussain (Tikrit Journal of Pure Science, 2018)
Geometric analysis of Al-Wind dam reservoir in Diyala discussed in this paper as necessary and strategic subject, spatial analysis systems were used to extract the area of Al-Wind dam reservoir from the digital elevations model (DEM), at 26 selected water levels in the reservoir with one meter interval, from 195 up to 219.5 m.a.s.l., the geometric criteria used to ​​extract the essential negative geometric elements represented by the Negative Volume (NV) Negative Planner Area (NPA) and Negative Surface Area (NSA), the perimeter of water body, the depth of water column and the shape factor of the reservoir, as well as for the positive geometric elements as Positive Volume (PV), Positive Planner Area (PPA) and Positive Surface Area (PSA) of the islands within the perimeter of the reservoir. The elements above are basics in geometric studies, which are used to design the procedure of reservoir operating, as the control on storage, and releases from the gates of the dam in the different operating conditions, it is control the changes that will occur on the land uses after beginning the storage at each level, as well as the changing on the outcrops of geological formations that would be inundated with changing in water level, accordingly, the secure operation level were determine to avoid the hazards on the dam, and decrease the wastage in the land use and the stored water, and decrease the immersed areas, the mathematical relationship between the inundated areas and the capacity of the reservoir were derived to use it in the future for the operation and routing of the reservoirs, determine the surface area of ​​the reservoir as well as predict the capacity of the reservoir at each level. The current analysis reflect that the maximum operational safe level is 215 m.a.s.l., that equivalent to the capacity of 54,308,822 m3, while the preliminary study of the dam, which was conducted using conventional methods to the survey indicated that the storage capacity at the same level is 37,820,000 m3. Digital elevations models for each selected level was exported as digital images of same scale for the purpose of visual comparison between the extensions and forms of the reservoir at different levels. This analysis useful to management of the dam used by the administration of the dam in the selection of suitable operational policy for the reservoir.